Tubercular Subdural Empyema with Tubercular Abscess: Lessons Learnt - Pannem, Rajkumar; Kanderia, Ridham Ashokbhai; Arora, Rajnish Kumar; Mittal, Radhey Shyam (Indian Journal of Neurosurgery, 2023)
Tuberculosis (TB) is still one of the major health care problems in many developing countries. Among various forms of TB, central nervous system (CNS) TB causes significant morbidity and mortality. CNS TB can present in various forms: cerebritis, abscess, meningitis, tuberculoma, calcified granuloma, meningitis, or hydrocephalus. But subdural empyema is a very rare form of presentation. Very few cases have been reported till now in the literature. So, high level of suspicion, thorough microbiological and histological investigations to diagnosis, and early and timely inception of anti-TB medication are keys in its management. Here, we are presenting a case of tubercular subdural empyema that was successfully treated with surgical evacuation and anti-TB medication.
Keywords: CNS; tuberculosis; subdural empyema; tubercular abscess